(untitled) (Gaceta Técnica, 2025)
The study reviews the ANSI/AISC 341-22 standard for the seismic design of industrial structures in Chile, comparing it with the Chilean standard NCh2369. Since Chile is a high seismicity zone, strict regulations are required to ensure structural safety. While NCh2369 emphasizes stiffness and energy dissipation through anchoring, AISC 341-22 prioritizes ductility through the formation of plastic hinges in beams. The seismic design of industrial structures is regulated by NCh2369, which recommends AISC as a complementary standard. However, both standards have different approaches to energy dissipation. AISC classifies structural elements as moderately or highly ductile to maximize their inelastic capacity. To evaluate the application of AISC 341-22, a rack-type structure was designed using this standard, applying NCh2369 for loads and seismic analysis. The modeling was done using Robot Structural Analysis 2024, optimizing structural profiles and verifying their compliance with regulations. One of the main findings was the detection of several W profiles that did not meet the requirements of AISC 341-22. The importance of early verification of slenderness was also highlighted to avoid reprocessing and adjustments in profile selection. Additionally, there was non-compliance with the displacement limits imposed by NCh2369 due to the difference in seismic demands between standards